Reinventing the Yggdrasil: Hilma af Klint and Political Aesthetics - Jadranka Ryle (InFormation: Nordic Journal of Art and Research, 2018)
The Yggdrasil, the holy tree of Norse mythology, is central to Hilma af Klint’s series of paintings from 1913/15: Tree of Knowledge. As with the Biblical Tree of Knowledge from Eden that is echoed in Christ’s cross, the Yggdrasil allows for the salvation of humanity in Norse mythology. During the nineteenth century, the Nordic National Romantic movement turned the Norse myth towards a politics of nationalism and nationhood. Taking as her point of departure these aestheticised nationalisms, af Klint’s abstraction redirects Nordic romanticism towards an alternative political aesthetic. Locating an intertwining of genders at the heart of the Yggdrasil tradition, her androgynous abstraction subverts the nationalist and patriarchal romanticism of the nineteenth century Yggdrasil.